2014
DOI: 10.1016/j.bbmt.2014.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Saliva from Patients with Oral Chronic Graft-Versus-Host Disease

Abstract: Chronic graft-versus-host disease (cGVHD) is an immune-mediated disorder and is the major long-term complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). The oral mucosa including the salivary glands is affected in the majority of cGVHD patients; however, at present there is only a limited understanding of disease pathobiology. In this study, we performed a quantitative proteomic analysis of saliva pooled from oral cGVHD(+) and oral cGVHD(-) patients using iTRAQ (isobaric Tags for Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 42 publications
0
31
0
5
Order By: Relevance
“…Involvement of the oral mucosa did not correlate with salivary dysfunction [107]. In the future, quantitative proteomic analysis of saliva may be added as a biomarker to identify active oral chronic GVHD, especially in newly diagnosed patients within the first 12 months after HCT [108]. Quantitative proteomic analysis of saliva from patients with and without oral chronic GVHD demonstrated altered expression in the chronic GVHD group with decreased IL-1 antagonist receptor and Cystatin B compared to the non-GVHD group.…”
Section: Histological Criteria For the Diagnosis Of Gvhdmentioning
confidence: 99%
“…Involvement of the oral mucosa did not correlate with salivary dysfunction [107]. In the future, quantitative proteomic analysis of saliva may be added as a biomarker to identify active oral chronic GVHD, especially in newly diagnosed patients within the first 12 months after HCT [108]. Quantitative proteomic analysis of saliva from patients with and without oral chronic GVHD demonstrated altered expression in the chronic GVHD group with decreased IL-1 antagonist receptor and Cystatin B compared to the non-GVHD group.…”
Section: Histological Criteria For the Diagnosis Of Gvhdmentioning
confidence: 99%
“…Two recent studies utilizing mass spectrometry approaches identified a total of 82 and 102 salivary proteins, respectively, that showed altered expression in oral cGVHD[80,81]. IL-1 receptor antagonist (IL-1ra) exhibited reduced expression in patients with oral cGVHD[80].…”
Section: Chronic Gvhd Biomarkersmentioning
confidence: 99%
“…IL-1 receptor antagonist (IL-1ra) exhibited reduced expression in patients with oral cGVHD[80]. The changes in IL-1ra expression coupled with higher levels of IL-1 family cytokines[16] in saliva likely enhance oral inflammation and subsequent tissue damage.…”
Section: Chronic Gvhd Biomarkersmentioning
confidence: 99%
“…The study used LC-MS/MS labeled free quantification for achieving the results [15]. Alteration of proteins associated with immune response was also found in another study performed with isobaric tags for relative and absolute quantification (iTRAQ) and tandem mass spectrometry (MS/MS) [16]. Additionally, two downregulated proteins were proposed as potential biomarkers: IL-1 receptor antagonist and cystatin B.…”
Section: Salivamentioning
confidence: 99%